2020
DOI: 10.1039/d0fo01643h
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol rich extracts of finger millet and kodo millet ameliorate high fat diet-induced metabolic alterations

Abstract: Taxifolin (98%) and catechin (86.6%) are the major polyphenols in KM-PRE and FM-PRE. FM-PRE and KM-PRE prevent obesity, hepatic steatosis, and gut bacterial dysbiosis however, the effects of KM-PRE are more profound compared to FM-PRE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“… 89 Millet shell polyphenols (MSPs) extracted from the cereal husks have anti-atherosclerotic effects in vitro . 90–92 Liu et al used ApoE-/- mice fed a high-fat diet as experimental subjects to investigate the anti-atherosclerotic activity of MSPs in vivo and found that MSPs effectively inhibited the development of atherosclerotic plaques, reduced the levels of related inflammatory factors, and significantly upregulated the expression levels of tight junction proteins (ocludin, zona occludens-1 and claudin 1) at the mRNA and protein levels; also, MSPs significantly altered the structure of mouse gut microbiota, in which Oscillospira and Ruminococcus were significantly enriched. 37 TOTUM-63 (T-63) is a polyphenol-rich plant extract that can have beneficial effects on the body weight and the insulin resistance in mice on a high-fat diet (HFD).…”
Section: Factors Affecting the Abundance Of Oscillospiramentioning
confidence: 99%
“… 89 Millet shell polyphenols (MSPs) extracted from the cereal husks have anti-atherosclerotic effects in vitro . 90–92 Liu et al used ApoE-/- mice fed a high-fat diet as experimental subjects to investigate the anti-atherosclerotic activity of MSPs in vivo and found that MSPs effectively inhibited the development of atherosclerotic plaques, reduced the levels of related inflammatory factors, and significantly upregulated the expression levels of tight junction proteins (ocludin, zona occludens-1 and claudin 1) at the mRNA and protein levels; also, MSPs significantly altered the structure of mouse gut microbiota, in which Oscillospira and Ruminococcus were significantly enriched. 37 TOTUM-63 (T-63) is a polyphenol-rich plant extract that can have beneficial effects on the body weight and the insulin resistance in mice on a high-fat diet (HFD).…”
Section: Factors Affecting the Abundance Of Oscillospiramentioning
confidence: 99%
“…However, only the kodo millet polyphenol extracts significantly increased the quantitative insulin sensitivity check index. Further analysis indicated that the extracts of finger millet chiefly included catechin, vanillic, chlorogenic, and protocatechuic acids whereas taxifolin acid was the main phenolic in kodo millet extracts (46). In addition, Ofosu et al reported that ethanol extracts containing soluble polyphenols of finger millet significantly increased inhibitory activity (IC50 = 18.07 µg/ml).…”
Section: The Relationship Between the Hypoglycemic Effect Of Millet P...mentioning
confidence: 99%
“…Epicatechin-3-gallate is a major catechin compound that showed beneficial effects in earlier reports of diabetes, Parkinson's disease, Alzheimer's disease, obesity, and stroke [56][57][58]. Khare et al [98] quantified 1.10 ppm concentration of catechin in kodo millets, which showed anti-obesity effects.…”
Section: Catechinmentioning
confidence: 99%
“…Naringin increases the alkaline phosphatase (ALP) activity [100], osteocalcin [101], and osteocalcin activity [102]. Khare et al [98] reported 11.97 ppm quantity of naringin in kodo millets with various health benefits.…”
Section: Naringinmentioning
confidence: 99%
See 1 more Smart Citation